Metabolic conversion of phenol to polyhydroxyalkanoate (PHA) for addressing dual environmental challenges: a review - Sabri, Izzati; Mohd Yusoff, Mohd Zulkhairi; Nor Muhammad, Nor Azlan; Ho, Li Sim; Ramli, Norhayati (Elsevier, 2025)
A sustainable approach to microbial polyhydroxyalkanoate (PHA) production involves utilizing waste as a substrate, which can include toxic pollutants like phenol as a carbon feedstock. Phenol-contaminated effluents offer cost-effective and readily available resources for PHA production, while simultaneously addressing phenol contamination issues. Understanding the metabolic conversion of phenol to PHA is crucial to enhance its efficiency, especially considering phenol's toxicity to microbial cells and the substrate-dependent nature of microbial PHA production. In this review, the mechanisms of phenol biodegradation and PHA biosynthesis are first independently elucidated to comprehend the role of bacteria in these processes. Phenol can be metabolized aerobically via various pathways, including catechol meta-cleavage I and II, catechol ortho-cleavage, protocatechuate ortho-cleavage, and protocatechuate meta-cleavage, as well as anaerobically via 4-hydrozybenzoate and/or n-caproate formation. Meanwhile, PHA can be synthesized through the acetoacetyl-CoA (pathway I), de novo fatty acids synthesis (pathway II), β-oxidation (pathway III), and the tricarboxylic acid (TCA) cycle, with the induction of these pathways are highly dependent on the substrate. Given that the link between these two mechanisms was not comprehensively reported before, the second part of the review delve into understanding phenol conversion into PHA, specifically polyhydroxybutyrate (PHB). While phenol toxicity can inhibit bacterial performance, it can be alleviated through the utilization of microbial mixed culture (MMC), which offers a wider range of metabolic capabilities. Utilizing phenol as a carbon feedstock for PHB accumulation could offer a viable approach to boost PHA's commercialization while addressing the issue of phenol pollution.